First description of a mortality event in adult Pacific oysters in Italy associated with infection by a Tenacibaculum soleae strain. Issue 2 (24th August 2017) - Burioli, E A V; Varello, K; Trancart, S; Bozzetta, E; Gorla, A; Prearo, M; Houssin, M
Abstract: Summer mortality episodes in adult Pacific oysters have been described since the 1950s in various farming areas. Starting in 2012, a recrudescence of mortalities in commercial‐sized oysters was first observed in France and then in Italy, with seasonality extension and translation later in the year. Moribund individuals collected during an event in Italy in December 2014 showed yellowish lesions of the mantle and adductor muscle. Histological examination revealed filamentous bacteria associated with necrotic areas. Quantitative PCRs targeting OsHV‐1 and Vibrio aestuarianus detected only high loads of the pathogenic bacteria in tissues of symptomatic individuals. A lower diversity of the hemolymph microbiota was also evidenced in moribund individuals, with a predominance of Vibrio and Arcobacter species. A strain of Flavobacteriaceae was isolated from all the symptomatic individuals. Sequence analysis of the 16S rRNA gene identified the strain as Tenacibaculum soleae . When strain pathogenicity was tested by injection in adult individuals, it induced mortality rates of up to 45%, even in the absence of V. aestuarianus . As mortality occurred only 11 days post‐infection, further investigation is needed to determine its effective virulence in natural conditions. This is the first description of a Tenacibaculum strain associated with bivalve mortalities.